EKSTRAKSI DAN KARAKTERISASI GELATIN KULIT IKAN BARONANG (Siganus canaliculatus) DENGAN METODE ENZIMATIS MENGGUNAKAN ENZIM BROMELIN: (Extraction and Characterization of Gelatin from Baronang’s (Siganus canaliculatus) Skin with Enzimatic Methode Using Bromelin Enzyme) - Dian Haryati; Lulu Nadhira; Humairah Hera; Nurlaila Abdullah (jurnal1, 2019)
Basically, gelatin is pure protein food ingredient, obtained from thermal collagen denaturation from animals. Gelatin is used as a stabilizer, gelling agent, binder, thickener, emulsifier, adhesive, whipping agent, and food wrap which is edible coating. Protein levels in fish skin determine the amount of collagen contained in skin tissue, so the baronang fish skin has a considerable opportunity as a source of collagen to be hydrolyzed into gelatin. This study aimed to determine the characteristics of gelatin produced from baronang fish skin by enzymatic extraction and to determine the best treatment of a combination of enzyme concentrations with extraction time. Making gelatine was carried out by hydrolysis using bromelin enzyme at a concentration of 1%, 1.5% and 2% with extraction time of 2 hours, 4 hours and 6 hours. The result, obtained gelatine with water content ranging from 3.13-5.83%, the water content ranged from 0.17-3.56%, ash content 0.35 - 3.65% and protein levels ranged from 91-94, 72%. The chemical characteristics of gelatine from baronang fish skin have a yield of up to 6%, water content <6%, ash content <4% and protein content reaching 94%. The best treatment was obtained at 1% enzyme concentration and extraction for 4 hours with a protein content of 94.72%.